Transient postoperative glycosuria after isoflurane exposure in two dogs. (15th February 2021) - Cha, J.; Shin, C. W.; Son, W.‐G.
Abstract : The present report describes two surgical cases involving the development of sudden glycosuria after isoflurane anaesthesia, despite the dogs having normal blood glucose levels and renal glucose reabsorption. The glycosuria manifested 1 day after surgery and resolved spontaneously within 2 days in both cases. Considering that the surgeries (subcutaneous mandibular mass removal and fracture repair) were unrelated to the kidneys, and there were no remarkable events during anaesthesia, the glycosuria may have been associated with the isoflurane anaesthesia. There have been several previous reports of glycosuria in human patients following transient proximal tubule dysfunction due to volatile anaesthetics. This case report suggests the possibility of transient renal dysfunction following isoflurane anaesthesia in these two clinically healthy dogs. However, considering the observational nature of this report, it can not be excluded that any other procedure performed in these animals was responsible of the observed glycosuria.